Peran Partai Politik Dalam Menentukan Kebijakan Yang Berkeadilan Di Indonesia - Nasarudin, Tubagus Muhammad (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The running of a country is certainly inseparable from a political system, because the political system is the benchmark for progress in a country. A developed country can be sure that the political system in it is well organized. The political system itself can be interpreted as a mechanism of a set of functions, where these functions are attached to political structures, in the context of implementing and making policies that bind society. In a political system there are various elements, and one of these elements is political parties. Political parties play an important role in the government system in a democratic country. In carrying out their roles and functions, political parties must uphold and implement an integrated political system. This research was conducted with a normative legal approach or legal literature study. The results of this study state that political parties are one of the important elements in the political system in a country. Especially in the process of making and implementing policies. In the process of making policies, political parties play a very large role, considering the involvement of political parties in the executive and legislative branches. In the process of implementing policies, political parties also have a role in the form of control over policies issued by the government, so that political parties are able to determine the direction of fair policies, namely prioritizing the interests of the people above all else